Preventive chemotherapy for the control of strongyloidiasis in school-age children: Estimating the ivermectin need. - Donal Bisanzio; Antonio Montresor; Michael French; Richard Reithinger; Paola Rodari; Zeno Bisoffi; Dora Buonfrate (PLoS Neglected Tropical Diseases)
Background Strongyloides stercoralis is a soil-transmitted helminth (STH) that affects approximately 600 million people worldwide. Interventions targeting S. stercoralis have not been implemented yet. Specific treatment (ivermectin) could be included in already ongoing preventive chemotherapy (PC) campaigns targeting other STHs. The aim of this study was to estimate the quantity of ivermectin needed for an integrated STH/S. stercoralis control program. Methododology/principal findings Our study estimates the number of school- age children (SAC) (the main focus of STH deworming campaigns) in need of PC with ivermectin. The normal approximation of the binomial distribution was adopted to calculate the hypothetical prevalence distribution in each endemic country. Considering prevalence thresholds for PC equal to 10%, 15%, and 20%, we estimated the number of SAC in need of treatment. We adjusted the estimates accounting for ivermectin distributed in lymphatic filariasis and onchocerciasis elimination programs and excluded from our calculation areas where Loa loa is endemic. The global number of SAC that should be targeted in PC campaigns was estimated at 283.9 M (95% CI: 163.4-368.8), 207.2 M (95% CI: 160.9-380.7), and 160.7 M (95% CI: 86.6-225.7) when the threshold for intervention was set to 10%, 15%, and 20%, respectively. India, China, Indonesia, Bangladesh, and Nigeria accounted for about 50% of the global SAC would have to be covered by PC intervention. Conclusions/significance Our analysis may support endemic countries to evaluate the ivermectin quantity needed for integrating strongyloidiasis in the existing STH programs. These estimates might also show to generic drug manufacturers the size of the potential market for ivermectin and encourage its production.